Emotion as Sensation and Feeling in Maupassant’s La Peur - Simay Turan (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The argumentation process is not exclusive to non-fictional texts. On the contrary, it has coexisted with narrative since the early stages of human history. From an anthropological point of view, primitive societies imposed social prohibitions and laws through narrative discourses - such as myths - to avoid a possible crisis within society and to ensure homo sapiens survival. In considering the narrative aspect of the argument, it would be appropriate to assume that literary discourse can constitute a certain argumentative reality. This article seeks to discover and verify the way a character affects its extratextual reader through the argumentation process. In Guy de Maupassant’s La Peur, a group of soldiers discuss the true meaning of the emotion of fear: indeed, they argue about it. The ethos constructed by the storytelling character and his way of expressing his emotions leads us to discover how fear’s literary expression can metamorphose into different states, like sensation and feeling, for the sake of making the storyteller legitimate in his discourse. The methodology of this article is based on narrative, enunciative and discursive analyzes to identify the argumentative reality in Maupassant’s La Peur.